2018
DOI: 10.1108/md-04-2017-0405
|View full text |Cite
|
Sign up to set email alerts
|

Organizational justice and work outcomes in the Kurdistan Region of Iraq

Abstract: Purpose-The purpose of this paper is to investigate the main and interaction effects of organizational justice components as they pertain to job performance and satisfaction in an Eastern region. Design/methodology/approach-Data were gathered utilizing a sample of 402 employee-manager dyads working for various institutions of higher education in the Kurdistan Region of Iraq. Hierarchical regression analyses and relative weight analysis were used to test the research hypotheses. Findings-The results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 61 publications
1
27
1
2
Order By: Relevance
“…Even though scholars highlighted the importance of organizational justice and its influence on innovative behaviour, empirical evidence about the same in non-western countries is limited and whether results from the research conducted at western countries can be generalized to eastern countries needs to be examined (Arab and Atan, 2018). The dearth of studies in non-western settings obstructs the extension or advancement of theoretical frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Even though scholars highlighted the importance of organizational justice and its influence on innovative behaviour, empirical evidence about the same in non-western countries is limited and whether results from the research conducted at western countries can be generalized to eastern countries needs to be examined (Arab and Atan, 2018). The dearth of studies in non-western settings obstructs the extension or advancement of theoretical frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of justice has been well established in studies of organizations (e.g. Arab and Atan, 2018; Singh and Singh, 2019; Zhang, 2015). Recent studies have also shown that the importance of justice transcends organizational boundaries and extends to interfirm outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As for the second effect, when the management respects its employees, the employees will be more committed and motivated to carry out their tasks (Porath, 2014;Arab & Atan, 2018). Findings also show that there is no managerial behaviour that has a greater effect on employees' motivation to work as the show of respect (Porath, 2014).…”
Section: The Mutual Respect Methods In the Motivation To Workmentioning
confidence: 99%